2023
DOI: 10.3390/w15050962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Organic Fertilizer of Ganoderma lucidum Residue on the Physical and Chemical Properties and Microbial Communities of Saline Alkaline Soil

Abstract: Saline-alkali land is the main reserve soil resource. The amount of arable farmland soil can be increased through improvement and utilization of saline-alkali land. Bio-organic fertilizer is an effective saline-alkali soil conditioner, but there are few studies on the improvement of saline-alkali soil with traditional Chinese medicine residues (TCMRs). In this study, an organic fertilizer made from Ganoderma lucidum residue (GLR) was mixed with saline-alkali soil at different proportions; physicochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Jia et al [45] discovered that vermicompost amendment can increase crop biomass accumulation and heavy metal transport and bioaccumulation in alfalfa, effectively improving the soil remediation efficiency. Deng et al [46] found, through laboratory and field experiments, that vermicompost-based amendments can significantly reduce the pH of Saline-Alkali soil and increase the SOM and available nutrients, findings that are consistent with the results of the current study. This may be because organic soil amendments can regulate nitrate flux in soil by reducing gaseous nitrogen loss and reducing nitrogen leaching, and hence improving soil fertility [47].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Jia et al [45] discovered that vermicompost amendment can increase crop biomass accumulation and heavy metal transport and bioaccumulation in alfalfa, effectively improving the soil remediation efficiency. Deng et al [46] found, through laboratory and field experiments, that vermicompost-based amendments can significantly reduce the pH of Saline-Alkali soil and increase the SOM and available nutrients, findings that are consistent with the results of the current study. This may be because organic soil amendments can regulate nitrate flux in soil by reducing gaseous nitrogen loss and reducing nitrogen leaching, and hence improving soil fertility [47].…”
Section: Discussionsupporting
confidence: 91%
“…Jia et al [45] discovered that vermicompost amendment can increase crop biomass accumulation and heavy metal transport and bioaccumulation in alfalfa, effectively improving the soil remediation efficiency. Deng et al [46] found, through laboratory and…”
Section: Discussionmentioning
confidence: 98%
“…In severe saline-alkali ecosystems, they will produce osmotic stress in bacteria and ultimately reduce and inhibit the active bacterial population and its quantity [28]. In our study, soil bacterial community richness increased in the R, H, and C treatments, which is similar to the results of Dong's study [1]. However, decomposed organic fertilizer significantly reduced the soil bacterial richness, which was the same as in Peng's study [5].…”
Section: Effects Of Organic Fertilizers With Different Degrees Of Mat...supporting
confidence: 85%
“…There is a large amount of uncultivated saline soil in China, and it is an important reserve of land resources. Finding ways to improve and manage these saline soils has become one of the emphases of future land use research [1]. Saline soil usually has a high salt content, a heavy soil texture, insufficient nutrients, and low microbial activity, which greatly limit the growth and development of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term plant cultivation could accelerate the process of soil desalination and maturation, causing fundamental changes in the properties of coastal saline land [28]. For alfalfa, when the planting duration increased, the biomass decreased, the consumption of soil nutrients reduced, the root-rhizobia symbiosis became more mature, the nitrogen fixation ability of plant roots enhanced, and a large number of plant residues decomposed into humus, therefore improving the soil quality.…”
Section: Discussionmentioning
confidence: 99%